The "Invisible Hand" of Economic Markets Can Be Visualized through the Synergy Created by Division of Labor. (18th December 2017) - Jaffé, Klaus
Abstract : Inspired by Adam Smith and Friedrich Hayek, economists promoting free markets postulate the existence of invisible forces that drive economic growth. Simulations with Sociodynamica allowed the emergence of market forces in virtual economies, showing that the synergistic working of division of labor in complex settings favors a stable state where all actors benefit (win-win interaction). By visualizing the detailed dynamics underlying this phenomenon in a simple virtual economy, the elements underpinning the synergistic effect on economic output produced by the division of labor between agents could be dissected. These are heterogeneity or spatial or temporal heterogeneous environment and/or agents; complementary activities of agents, with divergent optimization options; and synchrony. Markets help synchronize agent's actions. The larger the contact horizon between participants of the market is, the more efficient the market forces act. These features allow for social processes that increase the information available and increase simultaneously the capacity of producing useful economic work, that is, synergy. This insight, although trivial if viewed a posteriori, improves our understanding of the source and nature of synergies in real economic markets and might render economic and natural sciences more consilient.